2018
DOI: 10.1186/s12873-018-0209-y
|View full text |Cite
|
Sign up to set email alerts
|

Admission rates in emergency departments in Geneva during tennis broadcasting: a retrospective study

Abstract: BackgroundLiterature provides mixed results regarding the influence of large-scale sporting events on emergency department attendance. To contribute to the research on the subject, we sought to evaluate whether the broadcasting of major tennis tournaments, one of the most popular sports in Switzerland, has an impact on patient admission rates in emergency units in Geneva including 1) type of match 2) the role of a Swiss player, 3) degree of triage, 4) reason of attendance and 5) age of patients.MethodsAdmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…There has been some assumption that contact sport promotes aggression and violence, influencing the behaviour of fans beyond the match itself (Adubato, 2016;Kerr, 2005;White et al, 1992). However, the variety across the studies included in this review suggests that it is not limited to contact-only sports which support studies regarding tennis and Formula 1 (Correia et al, 2018;Piquero et al, 2021). If that is the case, more research is required to determine other factors connecting a major sports event and increased incidence of DV, such as whether it is the culture of the sport and the socio-demographics of those watching.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There has been some assumption that contact sport promotes aggression and violence, influencing the behaviour of fans beyond the match itself (Adubato, 2016;Kerr, 2005;White et al, 1992). However, the variety across the studies included in this review suggests that it is not limited to contact-only sports which support studies regarding tennis and Formula 1 (Correia et al, 2018;Piquero et al, 2021). If that is the case, more research is required to determine other factors connecting a major sports event and increased incidence of DV, such as whether it is the culture of the sport and the socio-demographics of those watching.…”
Section: Discussionmentioning
confidence: 94%
“…Research has so far shown that connections between major sports and assaults or crime more broadly are not necessarily the same across all sports or locations: following the broadcast of tennis in Switzerland admission rates to hospitals decreased (Correia et al, 2018), and no increase in (sex) crimes was seen following the Formula 1 Grand Prix in the United States (Piquero et al, 2021).…”
Section: Sports Events and Fan Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Intoxicated fans may only register the severity of their injuries after sobering up post-match [ 6 , 9 ]. In a retrospective study from Portugal examining Lisbon’s largest football Derby, 20% less patients were treated during the match.…”
Section: Discussionmentioning
confidence: 99%